17 years of experience with shunt systems in normal pressure hydrocephalus - From differential pressure to gravitational valves - Julian Zipfel; Cristina Kohlmann-Dell’Acqua; Susan Noell; Leonidas Trakolis (World Neurosurgery: X, 2024)
Objective: Complication rate of shunting for normal pressure hydrocephalus (NPH) has significantly improved over the last decades. Especially the use of overdrainage protection has reduced the incidence of subdural hematoma and collections. However, gravitational valves were associated with other complications of shunt dysfunction. We present our 17 years of experience with patients with normal pressure hydrocephalus who changed from a differential pressure valve to a gravitational valve system. Methods: We retrospectively identified all patients with the diagnosis of normal pressure hydrocephalus, in whom primary shunt implantation was performed between 2004 and 2020. Shunt implantation was performed as per our internal standard. Review of imaging, charts and patient reports was performed. Results: In total, 409 patients were included in the analysis. Mean age was 73.0 ± 7.1years. Between 2004 and 2010, predominantly Hakim valves (n = 100, 24.4%) were implanted, whilst from 2009 until 2020, proGAV valves (n = 296, 72.4%) were used. Mean follow-up was 8.9 ± 4.5 years. Initial subjective improvement of symptoms was reported in 69.9%, whilst this number decreased at the last follow-up to 29.8%. No significant differences were observed between the valves in the frequency of surgery for subdural hematoma. Shunt assistant implantation was performed in 17% of patients with Hakim valve, in 9.5% of patients with proGAV, a shunt assistant was added. Shunt obstruction was significantly higher in proGAV valves (p < 0.001). Conclusions: Our findings confirm the observation of frequent overdrainage in shunts without anti-siphon/gravitational component. Gravitational valves on the other hand may be associated with more obstruction.